Treatment of an Extensive Maxillary Cyst Using Nasal Airway and Balloon Catheter Devices - Atsushi Kasamatsu; Chonji Fukumoto; Morihiro Higo; Yosuke Endo-Sakamoto; Katsunori Ogawara; Masashi Shiiba; Hideki Tanzawa; Katsuhiro Uzawa (Case Reports in Dentistry)
Introduction. Large maxillary cysts occasionally expand into the maxilla and erode the maxillary sinus and nasal cavity. The Caldwell-Luc procedure is the recommended treatment for large maxillary sinus cysts. However, it is hard to preserve the nasal space in the case of large maxillary sinus cysts that penetrate into the nasal cavity. Methods. A 22-year-old man who had large maxillary sinus cysts was referred to our department for a surgical treatment. After removing the cyst from the maxillary sinus using the Caldwell-Luc procedure, we used nasal airway and balloon catheter devices to preserve the space of the inferior nasal meatus and maxillary sinus. These devices were removed 10 days postoperatively. Insertion and removal of both devices were simple and painless. Findings. The nasal airway and balloon catheter devices were useful for performing maxillary sinus surgery to remove large cysts. Our method was satisfactorily safe and was an effective minimally invasive treatment that preserved the space of the inferior nasal meatus and maxillary sinus.